Family ownership: does it matter for funding and success of corporate innovations? - Dorothea Schäfer; Andreas Stephan; Jenniffer Solórzano Mosquera (Small Business Economics, 2017)
Using the Mannheim innovation panel, we investigate whether family firms have higher financial need and how this affects both innovation input and innovation outcomes such as firm or market novelties, or process innovation. Applying the CDM framework, we find that family firms are more likely to have a latent financial need for innovation, which means that they have innovation ideas which they have not implemented yet. We find that family firms have a significantly lower marginal innovation productivity in particular for innovations with radical character, i.e., market novelties. We conclude from this evidence that family firms have a comparative disadvantage in innovation projects that imply high risk and require high innovation capability.
Keywords: D21; D22; G31; O30; O32; L26; 330; Innovation capability; Funding gaps; Financing restrictions; Family firms; CDM